2019
DOI: 10.1002/er.4734
|View full text |Cite
|
Sign up to set email alerts
|

Iron and nitrogen codoped carbon catalyst with excellent stability and methanol tolerance for oxygen reduction reaction

Abstract: Summary A series of non‐precious metal FexNC electrocatalysts for oxygen reduction reaction (ORR) were successfully synthesized using Fe(NO3)3, glucose, and melamine as the Fe, C, and N sources, respectively. The effects of the pyrolysis temperature and Fe/N contents on the catalytic performances are comprehensively investigated. Electrochemical results reveal that among the FexNC catalysts, Fe1.5NC‐900‐2 pyrolyzed at 900°C with the mass ratio of FeC to melamine being 1:10 proves the highest catalytic performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Nonetheless, these values were slightly lower than those of the commercial Pt/C catalyst, which is 0.97 V due to the small d band gap and few vacancies on the atomic transition state of Pt. The positive shift in the onset from 0.805 V with RGO 900 for all catalysts indicated that Fe metal and nitrogen play vital roles in creating active sites for ORR activity . The half wave potential was another parameter for determining the ORR activity of each catalyst.…”
Section: Resultsmentioning
confidence: 92%
“…Nonetheless, these values were slightly lower than those of the commercial Pt/C catalyst, which is 0.97 V due to the small d band gap and few vacancies on the atomic transition state of Pt. The positive shift in the onset from 0.805 V with RGO 900 for all catalysts indicated that Fe metal and nitrogen play vital roles in creating active sites for ORR activity . The half wave potential was another parameter for determining the ORR activity of each catalyst.…”
Section: Resultsmentioning
confidence: 92%
“…The increase in peak intensity was due to the accumulation of metal oxides on the catalyst surface. Analysis of the results (Figure 2) showed that as the reaction temperature increased, the metal oxides on the catalyst accumulated and this affected the electron transfer between iron and molybdenum oxides through the lattice oxygen and metal ions, and reduced the oxidation activity of the catalyst 37 . The selectivity of methylal decreased sharply, especially when the temperature increased to 663 K and this seriously affected the yield of the target product.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the results (Figure 2) showed that as the reaction temperature increased, the metal oxides on the catalyst accumulated and this affected the electron transfer between iron and molybdenum oxides through the lattice oxygen and metal ions, and reduced the oxidation activity of the catalyst. 37 The selectivity of methylal decreased sharply, especially when the temperature increased to 663 K and this seriously affected the yield of the target product. This also showed that the reaction temperature of this type of catalyst should be controlled at 663 K in the process of preparing methylal in a onestep process with methanol.…”
Section: Catalytic Crystal Structure and Microstructurementioning
confidence: 99%
“…Figure 5A and Table S2 exhibited that as-prepared catalysts mainly consisted of C, O, N, and Co. Nitrogen-doped acts a pivotal part in the electrocatalytic activity, which had been studied by numerous researchers. 39,40 The high-resolution N 1s spectrum of N-OMC, Co-N-OMC, and Co-N-3DOM/mC ( Figure 5B) could be fitted by four peaks corresponding to graphitic-N, pyrrolic-N, pyridinic-N, and pyridinic-N-oxide. [41][42][43] The high content of graphitic-N and pyridinic-N of Co-N-OMC and Co-N-3DOM/mC enhanced the catalytic performance.…”
Section: Characterization Of the Catalystsmentioning
confidence: 97%